Natural radioactivity in soil samples taken from Kahramanmaras provincial center - Kucukonder, Erdal; Gumbur, Serdar; Sogut, Omer; Dogru, Mahmut (Springer, 2023)
The levels of U-238, Th-232, and K-40 with gross alpha and beta values in soils collected from the Kahramanmaras city center were measured in this study, and the annual effective dose equivalent (AEDE), excessive lifetime cancer risk (ELCR), and terrestrial absorbed gamma dose rates were calculated for gamma radiation from U-238, Th-232, and K-40 radionuclides. The samples' gross alpha and beta radioactivity concentrations, respectively, range from 0.06 +/- 0.01 Bq/kg to 0.45 +/- 0.04 Bq/kg and 0.14 +/- 0.02 Bq/kg to 0.95 +/- 0.09 Bq/kg. The Kahramanmaras province's soil samples have mean gross alpha and beta radiation values of 0.25 +/- 0.03 Bq/kg and 0.52 +/- 0.05 Bq/kg, respectively. U-238, Th-232, and K-40 activity concentrations in soil samples range from 2.32 +/- 0.2 Bq/kg to 40.10 +/- 1.4 Bq/kg, 0.60 +/- 0.03 Bq/kg to 10.47 +/- 1.01 Bq/kg, and 11.60 +/- 1.01 Bq/kg to 160.84 +/- 4.6 Bq/kg, respectively. U-238, Th-232, and K-40 each had average activity concentrations of 11.50 +/- 1.1, 4.50 +/- 0.4, and 62.20 +/- 1.6 Bq/kg in soil, respectively. The annual effective dose equivalent (AEDE), excessive lifetime cancer risk (ELCR), and terrestrial absorbed gamma dose rate range from 0.01 +/- 0.01 mu Sv y(-1) to 0.03 +/- 0.02 mu Sv y(-1), and 0.01 +/- 0.01 x 10(-3) to 0.12 +/- 0.03 x 10(-3), 1.72 +/- 0.01 nGy h(-1) to 25.05 +/- 0.21 nGy h(-1), respectively. Additionally, the average annual effective dose equivalent (AEDE), average excessive lifetime cancer risk (ELCR), and average terrestrial absorbed gamma dose rates are 0.01 +/- 0.01 mu Sv y(-1), and 0.05 +/- 0.02 x 10(-3), 9.81 +/- 0.09 nGy h(-1), respectively. The acquired data were compared to both domestic and international standards.
Keywords: Kahramanmaras; Radioactivity in soil; Gross alpha and beta; Annual effective dose equivalent; Excessive lifetime cancer risk